Information ethics as a necessary element of the regulation of the modern information society - M. I. Korobko, (Ukrainian Cultural Studies, 2021)
The article is devoted to the analysis of the importance of information ethics in the active development of information and communication technologies. Active research on the issues of cyberspace has been conducted since the second half of the ХХth century. These studies are becoming more intensive every year. Many scientists are interested in analysis of these issues because communication plays the fundamental role in our dynamic modern world. Modern telecommunication technologies and, first of all, the global Internet, are one of the most important factors in the development of the world community, which has a decisive influence on the social, political, economic and socio-cultural spheres. And the global pandemic Covid-19 since 2020 has brought these issues to the forefront of socio-humanitarian research. The information space of the Internet, which has already become the main infrastructure of social communication at the local and global levels, is a relatively new cultural phenomenon. It is obvious that a clear and effective system of moral regulation in this area has not yet developed. This space provides a person with unprecedented opportunities in terms of personal freedom, challenging traditional moral attitudes. Of course, this raises many ethical issues, both general and applied, related to the spread of coercive and aggressive Internet advertising, pornography, violence, intrusion, privacy, and many other aspects. Computer technologies are not neutral. They are filled with human, cultural and social values. These values can be predicted and taken into account, they can appear and evolve after many trials and errors. In our multicultural world conflicting value system can often arise. Future research needs to do as much as possible to create a broader and more promising concept of what it means to be human in the stream of transformations that exist today. The solution of certain problems in information ethics is different depending on who solves these problems. All dilemmas and problems within the framework of the considered direction of applied ethics are open, and no one can give an exact answer to the questions yet. Thus, since in the modern information society there is a direct relationship between the intensity of technological development and the growth of crises in the field of moral values and spiritual culture, information ethics already makes a serious claim to the moral regulation of human behaviour.
Keywords: digitalization, etiquette, information ethics, information and communication technologies, netiquette